Early-onset neonatal infection in Lithuania - Rasa Tamelienė; Dalia Stonienė; Laura Russetti; Aušrelė Kudrevičienė; Virginija Gedvilienė; Rita Tvarijonavičienė; Albina Bulaukienė; Irena Nedzelskienė (Hygeia Press di Corridori Marinella, 2015)
Aim: The aim of the study was to analyze the etiology of early-onset neonatal infection (EONI), the risk factors, the forms and the time of its manifestation, and the tactics and outcomes of antibacterial treatment. Methods: During the prospective investigation, cases of newborns with diagnosed EONI and initial treatment in 2011 were analyzed. Four in-patient departments of Lithuania took part in the investigation. Results: In total, 18,778 newborns were included in the investigation. During the studied period, 209 cases of EONI were diagnosed: unspecified EONI in 168 (80.4%) neonates, pneumonia in 20 (9.6%), and early-onset sepsis (EOS) in 21 (10%) neonates. Group B Streptococcus (GBS) was responsible for 40% of microbiologically confirmed cases of sepsis. A negative blood culture was found in 11 newborns (52.4%) treated for sepsis. In all the cases, EONI was empirically treated with penicillin and gentamycin. The duration of antibacterial treatment varied between in-patient departments in Lithuania. During the studied period, 51.7% of women were screened for GBS colonization during pregnancy, and 21% of them had a positive vaginal culture for GBS; 78% of GBS carriers received intrapartum prophylactic antibiotics. Conclusions: The incidence of culture-confirmed early neonatal sepsis in Lithuania is similar to that indicated in the scientific literature, and is decreasing. Routine antenatal screening for GBS vaginal carriage in pregnant women is not universally performed in Lithuania. The duration of antibacterial treatment for EONI should be standardized in Lithuania.